A different justice: love and the future of criminal justice practice in America - DeValve, Michael J. (Carolina Academic Press, 2015)
The road behind, the road ahead -- Love and the followers of Jesus -- Other sacred perspectives on love -- Secular views on love -- That which can be remembered : core principles of love -- A tale of two icons : a selective history of criminal justice reform -- Policing in contemporary America -- Judging and punishing -- Justice through love -- A criminology of love -- From critique to compassion : a different justice